Exploring the Impact of Musealization on Spatial Vitality and Tourist Experience in the Historic Center of Macau - Xinyu Li; Pohsun Wang; Junling Zhou; Junyi Zhao (Buildings)
This study explores the enhancement of spatial vitality in the Historic Center of Macau from the perspective of museumification theory. This research employs GIS technology to analyze Baidu heatmap data, comparing the differences in spatial vitality between the festive and daily periods. Furthermore, experiential quality questionnaire data were collected from 224 tourists visiting the historical district, constructing a theoretical model of “objective vitality–experience quality”. Through objective analysis, the results indicate that the distribution of vitality in the Historic Center of Macau exhibits a clear core–periphery diffusion pattern. During the festive period, the intensity of spatial vitality significantly increases. Through subjective analysis, this study reveals that experiential quality has a significant impact on spatial vitality. Among the dimensions, education and inspiration, cultural exchange, and entertainment enjoyment have a notably positive effect on spatial vitality. The elements of education and inspiration play a crucial role during festive periods—particularly artistic attractions and educational entertainment—which positively influence vitality. This study innovatively applies museumification theory to the research of vitality in a historical district, providing valuable references for the sustainable cultural tourism development and cultural heritage preservation of the Historic Center of Macau.